The relationship of brand image and service quality on student loyalty of a university shop / Saida Farhanah Sarkam, Nurul Syafika Mohd Nasir and Shatina Saad - Sarkam, Saida Farhanah; Mohd Nasir, Nurul Syafika; Saad, Shatina (Universiti Teknologi MARA, Perlis, 2019)
The study aimed is to examine the relationship of brand image and service quality towards student loyalty in purchasing at a university shop, namely UniShop, in the southern state of Malaysia. By understanding student loyalty, the university management might encourage students to shop at the UniShop and generate revenues within the campus. The decreasing sales of UniShop are affected by a hypermarket located within walking distance to the university in August 2017. From the literature, the entrance of multinational companies might affect the small companies surrounding them, including UniShop which is a small enterprise. Thus, the research examined student loyalty in purchasing at UniShop by distributing questionnaires to the students of the university. The researchers used proportionate stratified random sampling to generalize the finding across all semester students in the university. The findings showed that brand image and service quality played an important role in student loyalty. Students were the main customers of a university shop, contributed most of the shop’s business sustainability, and generate indirect income to the university. In order to maintain student loyalty, UniShop has to take some initiatives including to increase the scale of products, focuses on student-centered services, improve the shop layout, and sell exclusive university merchandise to increase the student's self-belonging to the university products.